Regional Space: determining environment for systemic competitiveness - Pezo Paredes, Alfredo (2009)
In the last decade, Peru has taken significant steps in the process of decentralization in the field of technological innovation: the CITES network, Concytec's regional strategic groups and the FINCyT program to support research through a system of competitive funds. In this context, the urgency of sustainable and sustainable competitive regional development through technological innovation is highlighted.